Exploring Fungal Biodiversity in Crop Rotation Systems: Impact of Soil Fertility and Winter Wheat Cropping - Srdjan Šeremešić; Sonja Tančić Živanov; Miloš Rajković; Vladimir Aćin; Stanko Milić; Brankica Babec; Snežana Jovanović (Plants)
This study investigated soil fungal biodiversity in wheat-based crop rotation systems on Chernozem soil within the Pannonian Basin, focusing on the effects of tillage, crop rotation, and soil properties. Over three years, soil samples from ten plots were analyzed, revealing significant fungal diversity with Shannon–Wiener diversity indices ranging from 1.90 in monoculture systems to 2.38 in a fertilized two-year crop rotation. Dominant fungi, including Fusarium oxysporum, Penicillium sp., and Aspergillus sp., showed distinct preferences for soil conditions such as pH and organic matter (OM). Conservation tillage significantly enhanced fungal diversity and richness, with the highest diversity observed in a three-year crop rotation system incorporating cover crops, which achieved an average winter wheat yield of 7.0 t ha−1—47% higher than unfertilized monoculture systems. Increased OM and nitrogen levels in these systems correlated with greater fungal abundance and diversity. Canonical correspondence analysis revealed strong relationships between fungal communities and soil properties, particularly pH and calcium carbonate content. These findings highlight the importance of tailored crop rotation and tillage strategies to improve soil health, enhance microbial biodiversity, and boost agricultural sustainability in temperate climates, providing valuable insights for mitigating the impacts of intensive farming and climate change.